UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK TALK WRITE - Rosmaniar Sirait (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This research was conducted on grade VII students of SMP Negeri 4 Pangaribuan with the time to carry out activities in Odd Semester from July to August academic year 2018/2019. The purpose of this study was to determine the improvement in student learning outcomes by using the think talk write learning model on the introducing my self material in class VII-1 of SMP Negeri 4 Pangaribuan academic year 2018/2019. Data collection instruments were carried out using tests of student learning outcomes, and observations. The results of the study at the end of the first cycle were given a posttest, which obtained an average of 68.92, 19 students (63.33%) scored above the KKM. An increase in learning outcomes at the end of the second cycle given posttest, which obtained an average result of 78.83, ie 30 students (100%) or all students scored above the KKM of 70. The results of this research imply that the learning model of think talk write gives the impact of improving student learning outcomes for the better.                                                 Keywords: Think Talk Write, Introduce My Self  Abstrak: Penelitan ini dilakukan pada siswa kelas VII- SMP Negeri 4 Pangaribuan dengan waktu pelaksanaan kegiatan pada Semester Ganjil mulai bulan Juli sampai Agustus Tahun Pembelajaran 2018/2019. Tujuan penelitian ini untuk mengetahui peningkatan hasil belajar siswa dengan menggunakan model pembelajaran think talk write pada materi introduce my self di kelas VII-1 SMP Negeri 4 Pangaribuan T.P 2018/2019. Instrumen pengumpulan data dilakukan dengan menggunakan tes hasil belajar siswa, dan hasil pengamatan (observasi). Hasil penelitian pada akhir siklus I diberikan postest, dimana diperoleh hasil rata-rata 68,92, 19 siswa (63,33%) memperoleh nilai diatas KKM. Terjadi peningkatan hasil belajar pada akhir siklus II yang diberikan postest, dimana diperoleh hasil rata-rata 78,83, yaitu 30 siswa (100%) atau seluruh siswa memperoleh nilai diatas KKM yaitu 70. Hasil penelitan ini mengimplikasikan bahwa model pembelajaran think talk write memberikan dampak meningkatkan hasil belajar siswa menjadi lebih baik. Kata kunci: Think Talk Write, Introduce My Self